KAJIAN ANATOMIS AKAR DAN PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frutescens L.) PADA BUDIDAYA VERTIKULTUR DENGAN INTENSITAS BEDA PENYIRAMAN - , FITRIA RAHAYU RATMADANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The rapid increase in human population leads to reduce land productivity, especially in urban areas. The less of land area for growing plants tends to find the way use land efficiently to keep the productivity. Verticulture is a way of planting in a vertical arrangement up to the free air space, with the composition of the growth media also arranged vertically. Cayenne pepper (Capsicum frutescens L.) is one of the vegetables that is suitable to be cultivated with verticulture techniques. The demand increasing for chili consumption needs agribusiness strategy so that chili needs remain fulfilled. Thinking about the role of water is essential for plant life. Drought stress will have big impacts on the growth and productivity of plants. Growing cayenne pepper in verticulture with watering intensity variations would result incertain the root anatomical and physiological responses. This study aimed to examine the root anatomical and physiological responses of cayenne pepper in verticulture with various watering intensity. Chili seeds were in medium germinated. Fourteen days old seedlings (4-5 leaf emerged) were transferred to transplanting polybag as control (K) and vertical pots made of pipe with diameter of 9 inches and a height of 1 meter as treatment (P). During 35-days various watering intensity were given. Plants were watered every day (P1), for each 3 days (P3), and 6 days (P3). Plant height and number of leaves were measured and counted every week as growth parameters. Thirty five days old plants were harvested and observed, including length-width of leaves, chlorophyll content, fresh weight and dry root-shoots, and roots length. For anatomical parameters were measured root diameter, thickness cortex, stele and xylem diameter at the cross-section preparations. The results showed that the lower the watering was given, the root diameter, stele, xylem, and cortical thickness decreased. The less watering was given, then there was a decrease in plant height, leaf number, length-width of leaves, and wet and dry weight of rootshoots, but an increase of roots length and chlorophyll content of leaves cayenne pepper. Generally, plant growth decreased in less water given. Vegetative growth in polybag and verticulture did not show any significant difference, so that planting cayenne pepper in a verticulture is considered to be quite effective and applicable.